Morphological and Biochemical Features of Ovarian Tissue at Various Cryopreservation Modes - Trutaieva, Irina A.; Kiroshka, Viktoria V.; Gurina, Tatyana M.; Bondarenko, Tatyana P. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):177.